Enabling Always-Available Input with Muscle-Computer Interfaces - Saponas, Scott; Tan, Desney; Morris, Dan; Balakrishnan, Ravin; Turner, Jim; Landay, James A. (UIST '09 Proceedings of the 22nd annual ACM symposium on User interface software and technology, 2009)
Previous work has demonstrated the viability of applying offline analysis to interpret forearm electromyography (EMG) and classify finger gestures on a physical surface. We extend those results to bring us closer to using muscle-computer interfaces for always-available input in real-world applications. We leverage existing taxonomies of natural human grips to develop a gesture set covering interaction in free space even when hands are busy with other objects. We present a system that classifies these gestures in real-time and we introduce a bi-manual paradigm that enables use in interactive systems. We report experimental results demonstrating four-finger classification accuracies averaging 79% for pinching, 85% while holding a travel mug, and 88% when carrying a weighted bag. We further show generalizability across different arm postures and explore the tradeoffs of providing real-time visual feedback.